1984
DOI: 10.1007/bf01210729
|View full text |Cite
|
Sign up to set email alerts
|

On the curvature of piecewise flat spaces

Abstract: Abstract. We consider analogs of the Lipschitz-Killing curvatures of smooth Riemannian manifolds for piecewise flat spaces. In the special case of scalar curvature, the definition is due to T. Regge considerations in this spirit date back to J. Steiner. We show that if a piecewise flat space approximates a smooth space in a suitable sense, then the corresponding curvatures are close in the sense of measures.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
403
0
2

Year Published

1986
1986
2016
2016

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 339 publications
(411 citation statements)
references
References 23 publications
6
403
0
2
Order By: Relevance
“…Rigorous justification for this formula followed in [3], where it was shown that it converges to the continuum form of the action, in the sense of measures, provided that certain conditions on the fatness of the simplices are satisfied. Friedberg and Lee [4] approached the problem from the opposite direction, deriving the Regge action from a sequence of continuum spaces approaching a discrete one.…”
Section: A Basic Formalismmentioning
confidence: 99%
“…Rigorous justification for this formula followed in [3], where it was shown that it converges to the continuum form of the action, in the sense of measures, provided that certain conditions on the fatness of the simplices are satisfied. Friedberg and Lee [4] approached the problem from the opposite direction, deriving the Regge action from a sequence of continuum spaces approaching a discrete one.…”
Section: A Basic Formalismmentioning
confidence: 99%
“…Alternatively, of course the summation can be done over the points p, instead of the simplices s, (as in the exact expression of ref. [20] This second choice for the definition of C 2 (sum over sites) appears in fact more natural when one considers the coupling of gravity to matter fields, which will be represented here for simplicity by a scalar field ~(x). In the continuum an invariant action, up to terms quadratic in ~, is [4] Imatter = f d4x v/g [½g ~ 0fl~ 0~b +½m2@ 2 + gtR¢~ 2 -' 1"-g2 R~ 0tt~b 01, ~ n t-... ].…”
Section: Rtor(j) -[ A-~sv U~"u~ I(o[ # Up°uoomentioning
confidence: 99%
“…The version of the combinatorial Gauss-Bonnet theorem due to Cheeger, Müller and Schrader is essentially a quick calculation [38]. See also the paper by Charney and Davis [36] where they review this calculation and then use the resulting formula to find a combinatorial analogue of the Hopf conjecture in the context of nonpositively curved piecewise Euclidean n-manifolds.…”
Section: Combinatorial Gauss-bonnetmentioning
confidence: 99%